Maximizing the Role of Emergency Medical Services in COVID-19 Response. (20th December 2023) - Sonkin, Roman; Alpert, Evan Avraham; Katz, David E.; Jaffe, Eli
Abstract: The Centers for Disease Control and Prevention define 6 intervals of a pandemic: (1) investigation of cases, (2) recognition of the increased potential for ongoing transmission, (3) initiation of a pandemic wave, (4) acceleration of a pandemic wave, (5) deceleration of a pandemic wave, and (6) preparation for future pandemic waves. Each of these stages has 8 domains. Following China's coronavirus disease 2019 (COVID-19) outbreak announcement, Israel's National Emergency Medical Services (EMS) Organization immediately began working in conjunction with the Ministry of Health (MOH) to address the threat of the COVID-19 outbreak. This article will describe how a national EMS organization acted according to these pandemic intervals and domains. In the initial stages, EMS managed a checkpoint in the international airport voluntarily testing people for febrile symptoms. Calls to the dispatch centers that aroused the suspicion of COVID-19 resulted in EMS transport to the hospital with protective gear. During the period of first exposure, the scope of the medical emergency number was increased to include questions concerning coronavirus, telemedicine, and home sampling by protected EMS workers. In the contagion stages, epidemiological tests were conducted by the MOH, and EMS began operating dedicated telephone triage, mass drive-through sampling, and finally, administration of vaccinations.